4(2+3x)+11=-15-3 9-2(x-4)=2x+13 0.2(3y+2)=2.6y-1.6

BlaBla1aquamarine BlaBla1aquamarine    2   21.09.2019 01:10    0

Ответы
Siemens1 Siemens1  08.10.2020 05:56
(3)0.6y+0.4=2.6y-1.6
0.6y-2.6y=-1.6-0.4
-2y=-2
y=1

(2) 9-2x+8=2x+13
17-2x=2x+13
-2x-2x=19-17
-4x=-4
x=1

(1) -8-12x+11=-18
3-12x=-18
-12x=-18-3
-12x=-21
x= \frac{7}{4}
ПОКАЗАТЬ ОТВЕТЫ
Danil545333 Danil545333  08.10.2020 05:56
-4(2+3х)+11=-15-3
-8-12х+11=-18
-8+11+18=12х
21=12х
х=21/12
х=1,75 или х=1целая 3/4

9-2(х-4)=2х+13
9-2х+8=2х+13
9+8-13=2х+2х
4х=4
х=1

0,2(3у+2)=2,6у-1,6
0,6у+0,4=2,6у-1,6
0,4+1,6=2,6у-0,6у
2=2у
у=1
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика